MUSIC AS MEANS OF IMAGE FORMATION IN THE M. KULISH’S DRAMATURGY - Олексюк, Г. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article studies synthesis of music and literary art in the dramaturgy of Mykola Kulish. The author of the publication, through the prism of image formation, proves that in the whole range of plays of the prominent dramatist (“97”, “Sonata Pathetique”, “Narodnyi Malakhiy” and others) music is an important factor of creation of tempers of characters, impulsator of development of a dramatic act and conflict, as an aesthetic factor of dramas composition, as a means of enrichment of dramaturgical poetics.